Comfort index evaluating the water and thermal characteristics of proton exchange membrane fuel cell. (1st April 2019) - Wang, Renfang; Zhang, Guobin; Hou, Zhongjun; Wang, Keyong; Zhao, Yangyang; Jiao, Kui
Highlights: Comfort index is proposed to evaluate water and thermal characteristics. Comfort index is helpful to improve the water and thermal management. Cathode water flooding and anode membrane drying are determined quantitatively. Various operation conditions and design parameters are studied by comfort index. Abstract: Water and thermal management is of great importance to proton exchange membrane fuel cell. A comfort index is proposed to comprehensively evaluate the water and thermal characteristics in proton exchange membrane fuel cell. It refers to the concept of comfort index in meteorology and selects the cathode liquid water accumulation and anode membrane drying as two basic factors so as to prevent water flooding and low proton conductivity simultaneously. The anode and cathode comfort degrees corresponding to the anode membrane drying and cathode liquid water accumulation, respectively, are quantified and fitted at various operation conditions, of which the parameters in the calculation process are determined utilizing a carefully validated quasi-two-dimensional model. The influences of cathode stoichiometric ratio, operating pressure, coolant temperature difference, cathode relative humidity, coolant temperature, anode recirculating ratio, current density and membrane thickness at wide-range temperature are studied in detail by the comfort index. It is found that the comfort index usually first increases and then decreases with the increment of temperature, because the low water saturation pressure at low temperature makes the water condensation easier and thus leads to water flooding. Compared to analytical simulation models, the comfort index is able to instantly obtain the quantified water and thermal characteristics in proton exchange membrane fuel cell, which is of great significance to the stack design and in-situ system controlling in practical design.